2014
DOI: 10.1038/bjc.2014.203
|View full text |Cite
|
Sign up to set email alerts
|

The pro-apoptotic role of autophagy in breast cancer

Abstract: Background:Autophagy is a catabolic process that has a vital role in cancer progression and treatment. Current chemotherapeutic agents, which target autophagy, result in growth inhibition in many cancer types. In this study, we examined the role of autophagy in breast cancer (BCa) patients as well as BCa cell lines.Methods:Tissue microarray was used to detect the expression of an autophagy marker, LC3B in BCa patients (normal/hyperplasia=8; grade-I=15, grade-II=84, and grade-III=27) and BCa cell lines. To modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…Downregulation of the important autophagic proteins ULK and Beclin-1 often occurs in breast cancer, particularly in TNBC, suggesting that activation of autophagy may be beneficial [44]. Other studies suggest that a molecular switch is deciding the autophagy-mediated fate of the cells, and that increased autophagy above a threshold will force autophagic cell death [44][45][46]. As AEE788 is previously published to induce the pro-survival activity of autophagy [47], the observed increase in autophagic flux in our study could be an attempt to overcome the therapeutic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of the important autophagic proteins ULK and Beclin-1 often occurs in breast cancer, particularly in TNBC, suggesting that activation of autophagy may be beneficial [44]. Other studies suggest that a molecular switch is deciding the autophagy-mediated fate of the cells, and that increased autophagy above a threshold will force autophagic cell death [44][45][46]. As AEE788 is previously published to induce the pro-survival activity of autophagy [47], the observed increase in autophagic flux in our study could be an attempt to overcome the therapeutic stress.…”
Section: Discussionmentioning
confidence: 99%
“…LC3B staining is reported to be generally higher in tumor tissues than in normal tissues. 27,28 In estrogen receptor-negative BC, no association has been found between LC3B expression and androgen receptor expression and HER2 positivity.…”
Section: Discussionmentioning
confidence: 99%
“…11a–e For the experiment, the cells were treated with the dimethyl sulfoxide (DMSO) solution (final concentration of 0.002%) of the synthesized compounds and the cell viability was quantified using the trypan blue exclusion assay. 20 The natural product Psoralidin was used as a positive control and the vehicle (DMSO) as a negative control. Experiments on compound 14–15 and 25–28 showed that none of the compounds was able to carry out a reasonable inhibition of the growth of the cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…A collection of supernatants and adherent cells obtained by trypsinization were incubated in 0.4% trypan blue (Corning, Manassas, VA) at 1:1 ratio and pipetted onto a hematocytometer and manually counted under a microscope at ×20 magnification. 20 Psoralidin was used as a positive control and vehicle (DMSO) as a negative control.…”
Section: Methodsmentioning
confidence: 99%